2003
DOI: 10.1037/1089-2680.7.4.331
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Years of Social Psychology Quantitatively Described

Abstract: This article compiles results from a century of social psychological research, more than 25,000 studies of 8 million people. A large number of social psychological conclusions are listed alongside meta-analytic information about the magnitude and variability of the corresponding effects. References to 322 meta-analyses of social psychological phenomena are presented, as well as statistical effect-size summaries. Analyses reveal that social psychological effects typically yield a value of r equal to.21 and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

84
964
8
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,387 publications
(1,067 citation statements)
references
References 317 publications
84
964
8
11
Order By: Relevance
“…The direction of these effects is consistent with the notion that interracial interaction outcomes can be hindered by racial bias or intergroup anxiety (e.g., Dovidio, 2001;Shelton & Richeson, 2006b;Trawalter et al, 2009). At the same time, the magnitude of effect sizes was quite small, whether assessed with more traditional guidelines (Cohen, 1988) or recently developed empirically based guidelines (Hemphill, 2003;Lipsey & Wilson, 1993;Richard, Bond, & Stokes-Zoota, 2003). Richard et al, for example, examined hundreds of meta-analyses and found the average social psychological effect size to be r ϭ .21, while ours ranged from r ϭ .07 to .10.…”
Section: Discussionsupporting
confidence: 68%
“…The direction of these effects is consistent with the notion that interracial interaction outcomes can be hindered by racial bias or intergroup anxiety (e.g., Dovidio, 2001;Shelton & Richeson, 2006b;Trawalter et al, 2009). At the same time, the magnitude of effect sizes was quite small, whether assessed with more traditional guidelines (Cohen, 1988) or recently developed empirically based guidelines (Hemphill, 2003;Lipsey & Wilson, 1993;Richard, Bond, & Stokes-Zoota, 2003). Richard et al, for example, examined hundreds of meta-analyses and found the average social psychological effect size to be r ϭ .21, while ours ranged from r ϭ .07 to .10.…”
Section: Discussionsupporting
confidence: 68%
“…This subset of 11 studies was rated higher on contextual sensitivity (mean = 3.73) than studies in which the original researchers expected their results to be replicated successfully or in which they did not make a prediction about replication (mean = 2.80, P < 0.001). Although there are numerous reasons an author may express concerns about § A meta-analysis of 322 meta-analytic investigations of social psychological phenomena observed that the average effect in social psychology had an effect size of r = 0.21 (73). It is interesting that a similar effect of context holds even in this set of direct replication attempts.…”
Section: Resultsmentioning
confidence: 93%
“…However, it is important to note that contextual sensitivity does not necessarily suggest a lack of robustness or reproducibility. For instance, contextual variation is itself incredibly robust in some areas of research (73). Furthermore, contextual sensitivity is sufficient but not necessary for variation in the likelihood of replication.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the generalizability of results, we sought to recruit non-student samples and consider non-"WEIRD" (Western, Educated, Industrialized, Rich and Democratic) societies (Henrich, Heine, & Norenzayan, 2010). We sought to analyze datasets with at least 173 participants, which would provide 80% power to detect an effect of r = .21-the typical effect in social/personality psychology (Richard, Bond Jr., & Stokes-Zoota, 2003; see also Vazire, 2015).…”
Section: Overviewmentioning
confidence: 99%